Impacts of the walking environment on mode and departure time shifts in response to travel time change: Case study in the multi-layered Hong Kong metropolis - Chan, H-Y; Xu, Y; Chen, A; Liu, X (Elsevier, 2022)
Three-dimensional (3D) transportation space is one of the most important characteristics of multi-layered cities; however, fine-scale built environment factors about facilities that support the 3D walking environment were unavailable in understanding travelers’ behaviors before heading to the Big Data era. Using both small (questionnaire survey) and big (large-scale geospatial) data, we conducted a case study in Hong Kong, a well-known vertical metropolis with a multi-modal transportation system. We analyzed mode and departure time shift behaviors in response to travel time change for 2927 participants and examined the impacts of new variables derived from a 3D pedestrian network dataset and potential influencing factors identified in the literature. The results from the mode shift model indicated that having more efficient pedestrian networks, as measured by the total length of walkways and the provision of mobility aid facilities (e.g., travellators, escalators), is effective in promoting mode shift behaviors. Meanwhile, our departure time shift model revealed that having more comfortable walkways, as measured by travel attitude and the provision of mobility aid facilities, increases users’ willingness to make departure time shifts from peak hours. These findings imply that a more efficient and comfortable walking environment facilitates mode and departure time shift behaviors in daily travel. Improving the building and management of walking environments would contribute to a more integrated multi-modal transport system.